Evolutionary systematics of the Australian Eocyzicus fauna (Crustacea: Branchiopoda: Spinicaudata) reveals hidden diversity and phylogeographic structure. (4th August 2013) - Schwentner, Martin; Timms, Brian V.; Richter, Stefan
Abstract Although 'large branchiopods' are an important faunal element of the temporary water bodies in Australia's vast (semi)arid regions, knowledge of their diversity, distribution and ecology is still poor. Here, on the basis of one mitochondrial [cytochrome oxidase subunit I (COI)] and three nuclear (EF1α, ITS2 and 28S) markers, we present new data relating to the diversity and phylogeography of eastern and central Australian Eocyzicus (Spinicaudata) fauna. Using a combination of phylogenetic, haplotype network and DNA barcoding analyses of COI, 312 individuals were grouped into eleven main lineages. To infer whether these lineages are reproductively isolated from each other (the prerequisite for species delineation according to the Biological or Hennigian Species Concepts), separate analyses of each nuclear marker were performed on a subset of specimens. Although some lineages are non‐monophyletic in the analysis of one nuclear marker, this is mostly attributed to processes such as incomplete lineage sorting rather than ongoing reproduction. The eleven lineages translate into at least seven species whose reproductive isolation is additionally indicated by sympatry, including both Australian Eocyzicus species previously described. Another three lineages may constitute further species, but their clear allopatric distribution rendered the test for reproductive isolation inapplicable. One lineage appears not to be reproductively isolated and is therefore considered a genetically distinct lineage within one of the other species, and one divergent lineage within E. argillaquus may constitute an additional species. Although sympatry is very common – six species occur in the central Paroo River catchment in eastern Australia, for instance – syntopic occurrence is rare. It is possible that a combination of differing habitat preferences and priority effects inhibits the presence of more than one Eocyzicus species per water body. There is little to no genetic differentiation between certain populations of the species found in eastern and central Australia (e.g. the Murray–Darling Basin, the Bulloo River catchment and the eastern and northern Lake Eyre Basin; LEB), suggesting high dispersal rates within this large area. Between the central Australian populations themselves, however (e.g. those inhabiting the central and western LEB), genetic differentiation is pronounced, probably as a result of the lack of abundance of important dispersal vectors (aquatic birds) and the lower diversity and density of suitable habitats in the area. The most prominent biogeographical break exists towards north‐eastern Australia (north‐east LEB), which does not share species with any other region studied.